PELAKSANAAN HUMAS DALAM SOSIALISASI PROGRAM JAMINAN SOSIAL KETENAGAKERJAAN DI KANTOR BPJS KETENAGAKERJAAN PADANG - Sharly Yoenaz (Jurnal Ecogen, 2018)
The implementation of public relations in the socialization of the labor social security program at the BPJS Ketenagakerjaan Padang has not been carried out optimally because the socialization carried out does not cover all BPJS Employment stakeholders and socialization media that are underutilized optimally. The purpose of this study was to determine the implementation of public relations in the socialization of the labor social security program at the BPJS Ketenagakerjaan Padang. The method used is Qualitative Descriptive Research. Determination of Informants in this study was carried out with Snowball Sampling Techniques. Data collection is done through Observation, Interview and Documentation, with Model Data Analysis Techniques of Miles and Huberman. The findings in this study indicate that (1) the socialization of the labor social security program is not carried out directly to workers; (2) the lack of awareness of employers registering workers in the BPJS Ketenagakerjaan Padang program; (3) the media for socialization of the labor social security program has not been used optimally.Keyword: Public Relations, Socialization, Employment Social Security